Cancer spectrum in HIV-infected patients: A zonal hospital experience in Tanzania. (2020) - Mremi, Alex; Mswima, Jackline; Mlay, Mathew G.; Bartholomew, Henry; Alloyce, Julius P.; Mmbaga, Blandina T.; Bartlett, John
Highlights: HIV-infected people are living longer with better-controlled infection and they are experiencing higher incidence of chronic and age-related diseases including cancer. HIV infection has been associated with an increased risk of kaposi's sarcoma (KS), cervical cancer and non-Hodgkin's lymphoma (NHL); referred to as AIDS-defining cancers because of their association with increased risk of HIV infection. However, the spectrum of cancer diagnosis has been shifting from AIDS-defining to non-AIDS defining cancers since the introduction and widespread use of antiretroviral therapy (ART). In the current study, we found that the prevalence of cancer in HIV- infected patients was at 9% with non-AIDS defining cancers being much more common than AIDS-defining cancers suggesting an increased survival rates. We have seen the increasing trend of cancer prevalence in HIV-infected patients over time highlighting the need for tanzania to implement vaccination and screening programs which are important for cancer prevention and control not only in the vulnerable HIV-infected individuals, but also for the general population. We also recommend population-based studies in order to better describe the prevalence and spectrum of cancers in people living with HIV. Novel associations may become apparent as HIV-infected people are increasingly surviving (50 years and above) due to increasing access to ART. Such studies will provide a valuable tool for future investigations.. ABSTRACT: Background: Although the burden of human immunodeficiency virus (HIV) infection in Tanzania is high, limited data are available on cancers in HIV-infected patients. We aimed to determine the spectrum and prevalence of cancers in HIV-infected patients attending care at a zonal hospital in Tanzania. Materials and methods: Clinical records of HIV-infected patients from 2009 to 2019 were identified and retrospectively reviewed. Results: A total of 3398 HIV-infected patients were recruited with median age of 37 years. Cancer was diagnosed in 9% of the patients after enrollment into HIV clinical care, with an increasing prevalence from 7.2% between years 2009 and 2013 to 8.6% between years 2017 and 2019 ( p -value <0.0001). Majority (89.2%) were on antiretroviral therapy (ART) during the time of cancer diagnosis. The proportions of acquired immunodeficiency syndrome (AIDS)-defining cancers and non-AIDS defining cancers were 28% and 72% respectively. Kaposi's sarcoma was the most common (13.2%) AIDS-defining cancer while esophageal cancer was the most common (11.1%) non-AIDS defining cancer. The median duration of time from HIV infection to cancer diagnosis was 715 days (IQR: 98–2570). The median CD4 + T-cell count was 318(IQR 159–690) cells/µl at the time of cancer diagnosis and 40.7% of the patients had advanced immunosuppression with CD4 count less than 200 cells/µl at the time of cancer diagnosis. Conclusion: Non-AIDS defining cancers were much more common than AIDS-defining cancers suggesting increased longevity due to ART access. The prevalence of cancer among HIV-infected patients was 9% with an increasing trend over time; highlighting the importance of promoting cancer screening in this vulnerable population and implementation of vaccinations programs for liver and cervical cancers as well as tobacco control policies for smoking-related cancers.